Fermentative Production of N-Alkylated Glycine Derivatives by Recombinant Corynebacterium glutamicum Using a Mutant of Imine Reductase DpkA From Pseudomonas putida - Mindt, Melanie; Hannibal, Silvin; Heuser, Maria; Risse, Joe Max; Sasikumar, Keerthi; Nampoothiri, K. Madhavan; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2019)
Sarcosine, an N methylated amino acid, shows potential as antipsychotic and serves as building block for peptide-based drugs and acts as detergent when acetylated. N-methylated amino acids are mainly produced chemically or by biocatalysis, with either low yields or high costs for co-factor regeneration. Corynebacterium glutamicum ATCC 13032, which is used for the industrial production of amino acids for decades, has recently been engineered for production of N-methyl-L-alanine and sarcosine. Heterologous expression of dpkA in a C. glutamicum strain engineered for glyoxylate overproduction enabled fermentative production of sarcosine from sugars and monomethylamine. Here, mutation of an amino acyl residue in the substrate binding site of DpkA (DpkAF117L) led to an increased specific activity for reductive alkylamination of glyoxylate using monomethylamine and monoethylamine as substrates. Introduction of DpkAF117L into the production strain accelerated the production of sarcosine and a volumetric productivity of 0.16 g L 1 h 1 could be attained. Using monoethylamine as substrate, we demonstrated N-ethylglycine production with a volumetric productivity of 0.11 g L-1 h-1, which to the best of our knowledge is the first report of its fermentative production. Subsequently, the feasibility of using rice straw hydrolysate as alternative carbon source was tested and production of N-ethylglycine to a titer of 1.6 g L-1 after 60 h of fed-batch bioreactor cultivation could be attained.